Tumor targeting and imaging with dual-peptide conjugated multifunctional liposomal nanoparticles - Rangger C (Dove Medical Press, 2013)
Christine Rangger,1 Anna Helbok,1 Jane Sosabowski,2 Christian Kremser,3 Gottfried Koehler,4 Ruth Prassl,5,6 Fritz Andreae,7 Irene J Virgolini,1 Elisabeth von Guggenberg,1 Clemens Decristoforo11Department of Nuclear Medicine, Innsbruck Medical University, Innsbruck, Austria; 2Centre for Molecular Oncology, Barts Cancer Institute, Queen Mary University of London, London, UK; 3Department of Radiology, Innsbruck Medical University, Innsbruck, 4Department of Computational and Structural Biology, Max Perutz Laboratories, University of Vienna, Wien, 5Institute of Biophysics, Medical University of Graz, Graz, 6Ludwig Boltzmann Institute for Lung Vascular Research, 7piCHEM Research and Development, Graz, AustriaBackground: The significant progress in nanotechnology provides a wide spectrum of nanosized material for various applications, including tumor targeting and molecular imaging. The aim of this study was to evaluate multifunctional liposomal nanoparticles for targeting approaches and detection of tumors using different imaging modalities. The concept of dual-targeting was tested in vitro and in vivo using liposomes derivatized with an arginine-glycine-aspartic acid (RGD) peptide binding to αvβ3 integrin receptors and a substance P peptide binding to neurokinin-1 receptors.Methods: For liposome preparation, lipids, polyethylene glycol building blocks, DTPA-derivatized lipids for radiolabeling, lipid-based RGD and substance P building blocks and imaging labels were combined in defined molar ratios. Liposomes were characterized by photon correlation spectroscopy and zeta potential measurements, and in vitro binding properties were tested using fluorescence microscopy. Standardized protocols for radiolabeling were developed to perform biodistribution and micro-single photon emission computed tomography/computed tomography (SPECT/CT) studies in nude mice bearing glioblastoma and/or melanoma tumor xenografts. Additionally, an initial magnetic resonance imaging study was performed.Results: Liposomes were radiolabeled with high radiochemical yields. Fluorescence microscopy showed specific cellular interactions with RGD-liposomes and substance P-liposomes. Biodistribution and micro-SPECT/CT imaging of 111In-labeled liposomal nanoparticles revealed low tumor uptake, but in a preliminary magnetic resonance imaging study with a single-targeted RGD-liposome, uptake in the tumor xenografts could be visualized.Conclusion: The present study shows the potential of liposomes as multifunctional targeted vehicles for imaging of tumors combining radioactive, fluorescent, and magnetic resonance signaling. Specific in vitro tumor targeting by fluorescence microscopy and radioactivity was achieved. However, biodistribution studies in an animal tumor model revealed only moderate tumor uptake and no additive effect using a dual-targeting approach.Keywords: liposomal nanoparticles, radiolabeling, dual-targeting, tumor imaging, multifunctionality